Down-regulation of adhesion molecules and other inflammatory biomarkers after moderate wine consumption in healthy women: a randomized trial - Sacanella, Emilio; Vázquez-Agell, Mònica; Mena, Mari Pau; Antúnez, Emilia; Fernández-Solá, Joaquim; Nicolás, José Maria; Lamuela-Raventós, Rosa M; Ros, Emilio; Estruch, Ramón (The American journal of clinical nutrition, 2007)
BACKGROUND: Moderate alcohol consumption is cardioprotective. The mechanism for this beneficial effect might be reduced inflammatory responses, as suggested by prospective studies and small clinical trials in men. No studies have evaluated the antiinflammatory effects of wine in women. OBJECTIVE: We investigated whether low-dose intake of white and red wines has differential effects on inflammatory markers in women. DESIGN: In a crossover study, we randomly assigned 35 healthy women to two 4-wk periods of 20 g ethanol/d as white or red wine, preceded by two 4-wk washout periods. Before and after interventions, we measured serum lipids, circulating inflammatory biomarkers, cellular adhesion molecules (CAMs), and adhesion of monocytes to stimulated endothelial cells. RESULTS: HDL cholesterol increased, and the serum concentrations of high-sensitivity C-reactive protein, intercellular adhesion molecule-1, CD40L, and interleukin-6 decreased after either wine (P < 0.01, all). Vascular CAM-1 and E-selectin decreased (P < 0.01) only after red wine. CAM expression by mononuclear cells was blunted after either wine, with a greater suppressant effect of red wine. Enhanced adhesion of monocytes to stimulated endothelial cells was reduced by 51% (95% CI: -57%, -45%) after white wine and by 89% (95% CI: -96%, -82%) after red wine (P = 0.01 for between-wine differences). CONCLUSIONS: Moderate wine consumption is associated with beneficial effects on various inflammatory pathways related to endothelial activation in women. Probably because of its higher polyphenol content, red wine shows superior antiinflammatory effects than does white wine. Reducing low-grade inflammation and endothelial activation may be another potential mechanism by which alcoholic beverages exert their cardioprotective effect.